The relationship between supplementary services and customer satisfaction at Intekma Resort & Convention Centre (IRCC) / Siti Nur Ain Pardi - Pardi, Siti Nur Ain (2014)
The title of this research is “The Relationship between Supplementary Service and Customer’s Satisfaction at INTEKMA Resort & Convention Centre”. The purpose of this research is to see the relationship between the variables. There are three independent variables involve in this research which are hospitality, safekeeping of customer’s belonging, and providing information to customers. The dependent variable in this research is about customer’s satisfaction. In order to achieve this research, the hypothesis focuses on the objective to identify whether there is relationship between hospitality, safekeeping of customer’s belonging and providing information to customers towards customer’s satisfaction at INTEKMA Resort & Convention Centre (IRCC). In gathering the data, a set of questionnaire was distributed to customers at IRCC. Questionnaires were distributed to 150 respondents at IRCC. The frequency analysis, reliability test, descriptive analysis, Pearson’s correlation method and multiple regressions was used for data analysis. The result shows that three independent variables which are hospitality, safekeeping of customer’s belonging, and providing information to customers have significant relationship with the customer’s satisfaction at IRCC. The result also shown that one of independent variables which is hospitality become the most effective element of supplementary service towards customer’s satisfaction at IRCC.